2018
DOI: 10.1097/qmh.0000000000000187
|View full text |Cite|
|
Sign up to set email alerts
|

A Multidisciplinary Handoff Process to Standardize the Transfer of Care Between the Intensive Care Unit and the Operating Room

Abstract: Objective: Critically ill patients are at high risk for adverse events on transfer between intensive care unit and operating room. Patient safety concerns were raised within our institution during such transfers, and absence of a standardized patient handoff process was identified as an area of concern. Methods: The current state of the patient transfer processes between the intensive care units (ICUs) and the operating rooms (ORs) was mapped and failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Although the key tenets for hand overs are the same across all settings, each department has its own team composition, communication methods, policies, and challenges . Perioperative hand overs can be particularly complex because they involve personnel in multiple departments, patients who typically cannot take part in the process, and a vast amount of information; the environment can be noisy and chaotic; and personnel are often concurrently providing patient care . Brown said that other complexities can include time‐management issues and variances in staff member routines.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Although the key tenets for hand overs are the same across all settings, each department has its own team composition, communication methods, policies, and challenges . Perioperative hand overs can be particularly complex because they involve personnel in multiple departments, patients who typically cannot take part in the process, and a vast amount of information; the environment can be noisy and chaotic; and personnel are often concurrently providing patient care . Brown said that other complexities can include time‐management issues and variances in staff member routines.…”
mentioning
confidence: 99%
“…Despite the importance of effective hand overs, failures in the process remain a common problem . Errors can include a lack of focus or structure and transmission of too much, inaccurate, incomplete, or misinterpreted information, which can ultimately result in negative patient outcomes . Evidence has suggested that standardization of the hand‐over process can increase the accuracy of the information, enhance communication among personnel, and improve patient safety …”
mentioning
confidence: 99%
See 3 more Smart Citations